Understanding users formal meetings - Alliance of Bioversity International and CIAT (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
John Button and Louis Reymondin (Alliance of Biodiversity and CIAT - Data Driven Sustainability team.) Held a series of 4 formal meetings and other informal discussions with staff from the Hans R. Neumann Stiftung (the Trifinio Commission.